Alkaline-Alkaline Earth Fluoride Carbonate Crystals ABCO3F (A = K, Rb, Cs; B = Ca, Sr, Ba) as Nonlinear Optical Materials - Zou, Guohong; Ye, Ning; Huang, Ling; Lin, Xinsong (Journal of the American Chemical Society, 2011)
A new series of alkaline–alkaline earth fluoride carbonates (KSrCO3F, RbSrCO3F, KCaCO3F, RbCaCO3F, CsCaCO3F, and Cs3Ba4(CO3)3F5) were synthesized by spontaneous crystallization with molten fluxes. Their crystal structures, except for Cs3Ba4(CO3)3F5, exhibit the stacking of [AF]∞ (A = K, Rb, Cs) and [B(CO3)]∞ (B = Ca, Sr) layers, and the coplanar alignment of [CO3] triangles. The results from the UV–vis diffuse reflectance spectroscopy study of the powder samples indicated that the short-wavelength absorption edges were all below 200 nm, except for Cs3Ba4(CO3)3F5, which is about 210 nm. Second-harmonic generation (SHG) on polycrystalline samples was measured using the Kurtz and Perry technique, which indicated that these carbonates are all phase-matchable materials in both visible and the UV region, and their measured SHG coefficients were about 3.33, 3.33, 3.61, 1.11, 1.11, and 1.20 times as large as that of d 36 (KDP), respectively.